Adherence to Dietary Recommendations and Associated Factors Among Adults Aged 40 Years and Older with Type 2 Diabetes: A Cross-Sectional Study at Kericho County, Kenya - Joel Wanzala; Florence Wandia; Irine Chepngetich (Utan Kayu Publishing, 2026)
Type 2 diabetes is a major public health problem globally. There are limited data on adherence to dietary recommendations and its associated factors among type 2 diabetes patients, especially in Kericho, Kenya. Therefore, this study assessed the level and factors associated with adherence to dietary recommendations among type 2 diabetes patients aged 40+ years in Kericho County. A hospital-based cross-sectional study was conducted at Kericho County Referral Hospital in Kericho County, involving 414 type 2 diabetes patients aged 40+ years. Data was collected using validated and standardized structured questionnaires. SPSS version 26 was used to analyze data. Bivariate and multivariate logistic regression was used to identify factors associated with dietary adherence. Out of 414 participants, only 43.5% had good adherence to dietary recommendations. Multivariate logistic regression analysis showed that participants aged 70 years and above (AOR: 10.99, 95% CI: 1.61 – 25.08, p = 0.014), attained tertiary/college education (AOR: 8.20, 95% CI: 1.61 – 19.04, p = 0.021), no comorbidity (AOR: 2.78, 95% CI: 1.30 – 5.93, p = 0.008), had not experienced any complication (AOR: 3.09, 95% CI: 1.37 – 6.99, p = 0.007) had higher odds of good adherence to the recommended diet. Additionally, respondents with over 10 years since being diagnosed with diabetes (AOR: 0.57, 95% CI: 0.27 – 0.78, p = 0.024), had not received diabetes nutritional education (AOR: 0.15, 95% CI: 0.08 – 0.59, p <0.001), and lived with more than five family members (AOR: 0.43, 95% CI: 0.19 – 0.87, p < 0.001) had a lower likelihood of good adherence to dietary recommendations. The rate of dietary adherence was found to be relatively low in Kericho County, and significantly influenced with age, education level, comorbidity, diabetes-related complications, exposure to diabetes nutritional education and family structure. Provision and the implementation of structured and culturally tailored nutrition education using routine clinic-based counseling, standardized meal-planning guides, peer support groups, and regular dietitian follow-up to strengthen adherence and improve glycemic outcomes.